The effect of COVID-19 vaccination on symptomatic infection and related symptoms among preterm-born children aged 3–7 years in China - Dan Wang; Jia-Dong Ning; Jingke Cao; Changgen Liu; Shanghong Tang; Zhichun Feng; Tao Han; Li Li; Qiuping Li (Scientific Reports)
Abstract Vaccination plays a crucial role in preventing and controlling SARS-CoV-2 infections as well as their associated adverse outcomes. But there is a notable lack of research on the effectiveness of COVID-19 vaccination in children, particularly those young preterm-born children, who are more vulnerable to severe outcomes from SARS-CoV-2 infection. We aimed to determine the effect of vaccination with inactivated vaccines BBIBP-CorV and CoronaVac on symptomatic COVID-19 infection and related symptoms in preterm-born children aged 3–7 years after relaxation of the COVID-19 prevention and control measures in December 2022 in China. We performed a retrospective cohort study involving 242 preterm-born children aged 3–7 years and the data were collected in March 2023. Logistic regression models and modified Poisson regression models combined with entropy balancing were used to explore the associations of vaccination against SARS-CoV-2 with symptomatic COVID-19, specific symptoms, and persistent symptoms one month after recovery from COVID-19. Of the 242 recruited preterm-born children, 156 (64.5%) were vaccinated with inactivated vaccines BBIBP‐CorV and CoronaVac. After entropy balancing, the covariates were balanced between the vaccinated and the unvaccinated groups, with standardized mean difference < 0.001. Vaccination with the said SARS-CoV-2 vaccines lowered the risk of developing symptomatic COVID-19 in preterm-born children (risk ratio [RR] = 0.783; 95% confidence interval [CI]: (0.711, 0.861). Likewise, COVID-19 vaccination was associated with a decline in the risk of pneumonia (odds ratio [OR] = 0.318; 95% CI 0.110, 0.913), fever (RR = 0.710; 95% CI 0.635, 0.794), high fever (RR = 0.542; 95% CI 0.297, 0.988), sore throat (OR = 0.304; 95% CI 0.139, 0.664), and persistent symptoms (RR = 0.425; 95% CI 0.182, 0.993). Immunization with inactivated vaccines BBIBP‐CorV and CoronaVac provides protection against symptomatic COVID-19 for preterm-born children 3–7 years.